Exome sequencing confirms the clinical diagnosis of both joubert syndrome and klinefelter syndrome with keratoconus in a han Chinese family - Fang, Xinhe; Ma, Meijiao; Rong, Weining; Lian, Yuan-Yuan; Wu, Xueli; Gao, Yongying; Li, Hui-Ping; Sheng, Xunlun (Frontiers in Genetics, 2024)
Purpose This study was intended to identify the genetic etiology and determine the clinical diagnosis of one Han Chinese family with specific clinical manifestations of keratoconus and multiorgan involvement. Methods A comprehensive ocular and related general examination was performed on one patient and his asymptomatic parents and brother. Pathogenic genes were tested by exome sequencing. CNV-seq was used to verify the copy number variation, and peripheral blood was cultured for karyotype analysis. The Gene Expression Omnibus (GEO) dataset of keratoconus-related genes in the NCBI database was obtained to analyze the differentially expressed genes in corneal tissues of the keratoconus group and the normal control group, and analysis of protein-protein interaction networks (PPI) was performed. Results Proband, a 25-year-old male, had sudden loss of vision in the left eye for 1 week. Cranial magnetic resonance imaging (MRI) revealed changes in the midbrain and cerebellum, with a "molar sign" and a "bat-winged" ventriculus quartus cerebri. General check-up: 168 cm in height, decreased muscle tone in all four limbs, finger-to-nose test positive, intentional tremor evident in both hands, positive Romberg's sign, instability of gait, level I intellectual disability, poor adaptive behavior, communication disorders, hypotrichosis of beard and face, inconspicuous prominentia laryngea, and short upper and lower limbs. Exome sequencing detected compound heterozygous frameshift variants M1:c.9279dup:p.His3094Thrfs*18 and M2:c.6515_6522del:p.Lys2172Thrfs*37 in the patient's CPLANE1 gene and the presence of duplication-type CNV on the X chromosome. CNV-seq analysis showed the presence of a duplication-type CNV Xp22.33-Xq28 (2757837-156030895) of approximately 155Mb on the X chromosome of the proband. The two heterozygous frameshift variants and duplication-type CNV were pathogenic according to the ACMG guidelines. According to the genetic test results and clinical phenotype analysis, the family was finally diagnosed with Joubert syndrome combined with Keratoconus and Klinefelter syndrome. Conclusion In this study, we report a proband in a Han Chinese family with both Joubert syndrome and X-linked Klinefelter syndrome as well as keratoconus, and the phenotype spectrum of CPLANE1-Joubert syndrome may be expanded accordingly. Meanwhile, the significance of exome sequencing was emphasized in aiding the clinical diagnosis of complex cases, which is difficult to make.